Peran Dinas Perhubungan Kabupaten Cilacap Dalam Pembinaan Juru Parkir Di Wilayah Kota Cilacap - Wahyu Hariadi; haris kusuma wardana haris; Agoes Djatmiko (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
Parking is one of the components or inseparable aspects of the needs of the transportation system, because every trip by private vehicle generally always starts and ends at the parking lot. Basically parking is a public need that initially functions to serve. In accordance with this function, parking space is adjusted according to demand in line with the needs of people who drive to be in or access a place. Regarding parking, it has been regulated in Article 1 of Law Number 22 of 2009 concerning Road Traffic and Transportation, which reads: